Evatuation of different products used to manage Prodiplosis Iongifilci (Diptero: Cecidomyiidae) infesting tomato (Lycopersicum esculentum) crops in Valle del Cauca, Colombia - DELGADO-S., ALEXANDRA; MESA, NORA CRISTINA; ESTRADA, EDGAR IVÁN; ZULUAGA, JOSÉ IVÁN (Revista Colombiana de Entomología, 1999)
The midge Prodiplosis longifila is now a major pest of tomato in the Department of Valle del Cauca, Colombia. It penetrates flower buds, provoking them to fall and thus preventing fruit formation, and also damages already formed fruits. This pest is usually managed with frequent applications of expensive agrochemicals. In searching for a more rational method of controlling this insect, this study analyzed the following products for efficacy: Bionim, Bacillus thuringiensis var. kurstaki (Dipel 2x (R)). Bacillus thuringiensis var. israelensis (VectoBac (R)), Biomel, Micobiol, and a mixture to Dipel 2X and nereistoxina hidroxalato (Evisect (R)). Also included were a check using farmers' practice (chemical inputs) and an absolute check (no controls, to compare pest damage on different plant structures). The experiment was conducted on a commercial crop over two cropping seasons. Each experiment plot had 50 plants with three replicates per treatment. Productos were applied twice a week. Results indicated that P. longifila attacked leaf shoots, leaves, and flower buds, regardless of treatment and during the entire crop cycle. Two treatments –Biomel and farmers' practice—offered significantly better control of the midge, reducing damage levels in tender shoots and flower buds, than did the other treatments. Fully formed tomato fruits were also attacked by P. longifila, although no so severely as the fruit borer (Neoleucinodes elegantalis).